Pengaruh drill pukulan menggunakan dumbbell terhadap power otot lengan dan kecepatan pukulan atlet iba mma undikma camptahun 2022 - Yossa Irbhanora; Baiq Satrianingsih; Tiassari Janjang Suminar (Jurnal Pengetahuan dan Pendidikan, 2024)
Mixed martial arts or better known as Mixed Martial Arts (MMA) is a contact sport that allows various fighting techniques, such as grappling, kicks and punches. The purpose of this study was to determine the effect of punch drill exercises using dumbbells on arm muscle power and striking speed of IBA MMA UNDIKMA CAMP athletes in 2022. The method in this study used an experimental method with a research design using the One-Group Pretest-Posttest Design form, where this study there is an initial test then given treatment (treatment) in the form of dumbbell weight training then a final test is carried out to find out the results of the study. This research was conducted on IBA MMA UNDIKMA CAMP athletes with a total population of 25 people. In this study, 16 people were taken as samples using purposive sampling technique. The instrument used in this study was a Two-Hand Medicine Ball Put and hitting speed of 30 seconds.The results of the hypothesis stated "there is an effect of punch drill exercises using dumbbells on arm muscle power and speed (frequency) of strokes of IBA MMA UNDIKMA CAMP athletes in 2022. Where the t-count value of arm muscle power athletes of IBA MMA UNDIKMA CAMP in 2022 is 2,150 and compared with the t-table value at a significant level of 0,5% with degrees of freedom (df), namely n-1 = 16-1 = 15 is 1.753, it is known that the t-count value is greater than the t-table value, namely = 2,150> 1.753.The t-count value for the speed (frequency) of hitting IBA MMA UNDIKMA CAMP athletes in 2022 is 14,901 and when compared with the t-table value at a significant level of 0,5% with degrees of greatness (df), namely n-1 = 16-1 = 15 is 1.753,